The Retirement Decision in OECD Countries - Blöndal, Sveinbjörn (OECD Publishing, 1999)
This paper examines the main determinants of the decision to retire from the labour market in OECD countries, and in particular the role of social security systems in driving down the labour-force participation rate of older people in recent decades. It demonstrates that old-age pension systems in virtually all OECD countries in the mid-1990s made it financially unattractive to work after the age of 55, and the implicit tax on continued work has risen strongly since the 1960s in most countries. Financial disincentives to continued work have been amplified by various de facto early-retirement programmes, including unemployment-related and disability schemes. Pooled cross-country time-series regressions show that increased disincentives to work at older ages have contributed significantly to the drop in labour-force participation rates of older males, but also demonstrate that the deterioration of labourmarket conditions in many countries has played a significant role as well ...
Keywords: Economics